Christy Angelle Bauman's Theology of the Womb Perspective on Contributing to the Fatherless Phenomenon - Bram M, Prionaray; Karusisi, Ester Tadu; Rendi, Yosep (STT Transformasi Indonesia Manado, 2025)
Indonesia ranks third in the world as a country experiencing the pressure of the fatherless phenomenon. Indonesia is experiencing a crisis of the presence of a father in the development of children, resulting in the term for Indonesia as a fatherless country. As citizens, believers must also need to reflect on this phenomenon and contribute ideas to the phenomenon of fatherlessness, because of its enormous impact on child development, both biologically and psychologically. The research method used in this study uses a qualitative research method with a literature study approach. The purpose of this study is to correlate the theology of mercy of Christy Angelle Bauman with the phenomenon of fatherlessness, as a very sad condition in Indonesia until now according to data for 2023. In this study, it was found that the theology of Christy Angelle Bauman, emphasizes the task of mercy that is not directed at the biological understanding that must be carried out by mothers only, but also a father and with the aim of breaking out of the patriarchal culture that continues to shackle